Peran Kepala Sekolah dalam Mengelola Sumber Daya Manusia untuk Meningkatkan Mutu Pendidikan di SMAN 5 Payakumbuh - Fatma Sari; Zulfani Sesmiarni; Susanda Febriani (Politeknik Kampar, 2024)
Efficient human resources management is essential for the effective functioning of educational institutions. Therefore, it is essential for the head of school to have a clear approach to managing human capital effectively within educational institutions. It is essential to improve educational standards and enable institutions to effectively compete with others in the field of technological advances and contemporary developments. The study uses descriptive qualitative methodology, specifically using case study research design. The location of this research is in SMAN 5 Payakrasuh. The analysis revealed that the head of school carefully implemented a series of actions to establish a human resource management strategy for teachers. The first step involves developing a strong character, understanding the purposes and objectives of the institution, enhancing the expertise of the instructor, encouraging partnerships with other institutions, and building efficient communication with student guardians. One measure involves enhancing human resource development by conducting workshops and courses, both inside and outside the institution. The main emphasis lies on the methodology used by the head of school in overseeing instructors to improve the caliber of secondary education institutions. Quality education strategies in educational institutions are developed by involving instructors and implementing internal and external initiatives. The main challenge faced by school administrators in implementing their strategy is the existence of instructors who are satisfied with their existing level of expertise and resist to acquire new knowledge. Therefore, teachers must have strong motivational abilities to inspire these educators to enhance their talents, along with a deep understanding of their psychological conditions to optimize their performance.